Recent Publications (Quarterly Journal of Economics, 1945)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 59, Issue 3, May 1945, Pages 477–481, https://doi.org/10.1093/qje/59.3.477 Published: 01 May 1945